Answer:
x = π n_1 + π/6 for n_1 element Z
or x = π n_2 - π/6 for n_2 element Z
Explanation:
Solve for x:
1 - 3 tan^2(x) = 0
Subtract 1 from both sides:
-3 tan^2(x) = -1
Divide both sides by -3:
tan^2(x) = 1/3
Take the square root of both sides:
tan(x) = 1/sqrt(3) or tan(x) = -1/sqrt(3)
Take the inverse tangent of both sides:
x = π n_1 + π/6 for n_1 element Z
or tan(x) = -1/sqrt(3)
Take the inverse tangent of both sides:
Answer: x = π n_1 + π/6 for n_1 element Z
or x = π n_2 - π/6 for n_2 element Z